Ionic Surfactant Enhancement of Clay Properties for Heavy Metals Adsorption: Kinetics and Isotherms - Adekeye Damilola Kayode; Asaolu Samuel Sunday; Adefemi Samuel Oluyemi; Ibigbami Olayinka Abidemi; Akinsola Abiodun Folasade; Awoniyi Marcus Gbolahan; Popoola Olugbenga Kayode (Universitas Gadjah Mada, 2021)
The global health problems arising from ingesting toxic metals necessitate the quest for developing efficient materials for their remediation. Surface properties of raw kaolinite clay collected from Ire-Ekiti, South-western Nigeria, were improved by modification using sodium dodecyl sulphate (SDS) for the adsorptive removal of Pb, Cr, Ni and Cu from their respective aqueous solution. The raw and modified clays were characterized by X-ray fluorescence, Fourier transformed infrared spectrometry, Scanning electron microscope coupled with EDX and Particle induced x-ray emission technique. A batch adsorption study was used to examine the performance efficiency of the modified clay. Optimization of adsorption conditions like temperature, particle size, concentration, agitation time and pH was performed. The clay after modification showed improved surface properties such as increased pore diameter and number. Freundlich, Langmuir and Temkin isotherm models were applied to explicate the adsorption processes, while Pseudo-First order, Pseudo-Second order and the Elovich kinetic models were used to predict possible mechanisms driving the adsorption processes. The adsorption processes driven by chemical mechanisms involved series of complex mechanisms that include ion exchange, direct bonding and surface complexation other than precipitation. The percentage removal of the metals by the modified clay soil reached the values of 98.53, 94.50, 73.82, and 80.40 for Pb, Cu, Ni and Cr.